TANGGUNG JAWAB KELUARGA DALAM PENDIDIKAN ANAK DI ERA KOSMOPOLITAN (Tela’ah Tafsir Kontemporer Atas Surat At-Tahrim Ayat 6) - Arie Sulistyoko (IQRO: Journal of Islamic Education, 2018)
In an effort to produce a strong and quality future generation, there needs to be consistent and continuous efforts from parents in carrying out the task of nurturing, nurturing and educating their children physically and mentally until the child is mature and / or can stand alone, where the task this is the obligation of parents. The issue of child care and care is a problem related to the protection of children's own welfare in an effort to improve the quality of children in their growth, and prevent the neglect and unfair treatment to realize children as humans who are whole, resilient, intelligent and virtuous. So, shelter for children is parents. in the lives of people everywhere, families are the smallest unit with a very large role. A very big role is caused, because the family has a very important function in the continuity of people's lives. The process of knowing the rules and values adopted, for the first time was obtained in the family.